Characteristics and Formation of the Luzon Undercurrent in the Western North Pacific: Observational Study. Issue 7 (22nd July 2022) - Li, Junlu; Gan, Jianping
Abstract: The subsurface circulation system in the western North Pacific is dominated by the convergence of the Luzon Undercurrent (LUC) and the Mindanao Undercurrent, which forms the basin‐scale eastward North Equatorial Undercurrent jets. The southward LUC, situated to the east of Luzon Island, plays a significant role in transporting subsurface waters equatorward in the western boundary of the subtropical North Pacific. Despite its crucial contributions to the water, heat, and energy distributions in the subsurface layer, its characteristics and formation mechanism remain unclear. In this study, we utilize monthly climatological temperature and salinity data and the derived geostrophic velocity to investigate the spatiotemporal variability of the LUC and its formation dynamics. The LUC transport exhibits weak seasonality and strong intra‐seasonal variation, peaking in May/June and October. The origin of the LUC is closely connected with the southward veering of the Deep North Equatorial Current (DNEC) off the Ryukyu Islands and the Luzon Strait middle‐layer outflow (LSMO). The DNEC dominates transport in the LUC, and the LSMO of the South China Sea (SCS) Intermediate Water contributes to the water mixing in the LUC. Locally, the appearance of the LUC is dynamically linked with the barotropic effect associated with the sea surface height gradient and the baroclinic effect raised from the downward tilting of the zonal isopycnal off the Philippine coast. Spatially, the core of the LUC shifts from in‐shore to off‐shore waters from May/June to October. This study reveals the spatiotemporal characteristics of the LUC and identifies its separate origins from the interior North Pacific and the SCS middle layer. Plain Language Summary: In the tropical western North Pacific, the North Equatorial Current bifurcates at the Philippines east coast into two western boundary currents, Kuroshio and Mindanao Current, in the upper ∼500 m water depth. This circulation distributes the subtropical water meridionally and plays a significant role in the global ocean circulation and climate change. Below the upper layer circulation, the undercurrent system in 500–1, 500 m is critical to the subsurface volume, heat, and salt transport in this region. Among them, the Luzon Undercurrent (LUC) is the most important pathway of the southward subsurface water in the western boundary of the tropical North Pacific. LUC has been widely investigated in the previous studies. However, due to the limitation in the resolution and coverage of the observation data, the characteristics of the LUC and its origins have not been clearly revealed. This study investigates the origins, spatiotemporal variability of the LUC, and its inter‐connection with the adjacent subsurface currents. We clarified the spatiotemporal variation of the LUC and its physical linkage with adjacent marginal sea and open ocean. We demonstrated the origins of the LUC in different periods in a year and provided a dynamic interpretation for the formation mechanism of the LUC. Key Points: The Luzon Undercurrent (LUC) is contributed to and characterized by waters from the Deep North Equatorial Current and Luzon Strait middle‐layer outflow, and is locally sustained by baroclinic forcing Temporally, the LUC intensity has weak seasonality and significant intra‐seasonal variation, with two peaks in May/June and October Spatially, the LUC shifts from in‐shore to off‐shore from early summer to late fall, originating from the interior North Pacific and South China Sea middle layer, respectively